2021
DOI: 10.1371/journal.pone.0247197
|View full text |Cite
|
Sign up to set email alerts
|

Association of proangiogenic and profibrotic serum markers with lung function and quality of life in sarcoidosis

Abstract: Background Sarcoidosis is a systemic inflammatory granulomatous disease, frequently affecting the lung. If left untreated, it may end in lung fibrosis. Proangiogenic and profibrotic vascular endothelial growth factor (VEGF), transforming growth factor (TGF)-β1, fibroblast growth factor (FGF)-2 and platelet-derived growth factor (PDGF)-AB are a known therapeutical target in pulmonary fibrosing diseases, e.g. IPF, but there is no targeted therapy option for pulmonary fibrosis in sarcoidosis. Objectives The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Another non-canonical observation was that all cardiac endothelial cells upregulated tissue remodeling pathways, such as TGFβ and ECM signaling, relative to control. This is certainly not a novel thought as many studies have showed that endothelial cells can have pro-fibrotic functions (53), but this suggests that histological fibrosis reported in CS might be the result of the concerted action of fibroblasts and endothelial cells. Thus, we show that cardiac endothelial cells exhibit upregulated angiogenic and pro-inflammatory phenotypes in CS relative to control.…”
Section: Discussionmentioning
confidence: 97%
“…Another non-canonical observation was that all cardiac endothelial cells upregulated tissue remodeling pathways, such as TGFβ and ECM signaling, relative to control. This is certainly not a novel thought as many studies have showed that endothelial cells can have pro-fibrotic functions (53), but this suggests that histological fibrosis reported in CS might be the result of the concerted action of fibroblasts and endothelial cells. Thus, we show that cardiac endothelial cells exhibit upregulated angiogenic and pro-inflammatory phenotypes in CS relative to control.…”
Section: Discussionmentioning
confidence: 97%
“…PDGF-AB was associated with decreased health-related QoL. These mediators may represent a prognostic and therapeutic target for sarcoidosis as a brotic lung disease beyond IPF [115].…”
Section: The Hotspots and Frontiersmentioning
confidence: 89%
“…In a separate study involving 54 patients, an association was found between lung function and serum levels of PDGF-AB and VEGF in individuals with sarcoidosis. However, VEGF concentrations did not differ significantly among patients with sarcoidosis, idiopathic pulmonary fibrosis (IPF), or controls [92]. An investigation into B cell-activating factors (BAFFs) in plasma levels conducted on 55 sarcoidosis patients revealed the following (90).…”
Section: Serum Biomarkersmentioning
confidence: 99%